Pelatihan dan Pendampingan Strategi Pembelajaran Literasi Numerasi Bagi Guru Sekolah Dasar untuk Menghadapi Tantangan Kurikulum Merdeka - Susandi, Ardi; Sudirman, Sudirman; Wahyuningrum, Endang; Jusniani, Nia; Yumiati, Yumiati; Mustikaningsih, Dian (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia, 2025)
The low achievement of numeracy literacy among Indonesian students, as reflected in the results of the National Assessment and the Programme for International Student Assessment (PISA), presents a serious challenge in improving the quality of basic education. This condition demands the strengthening of teacher competencies so that they are able to design numeracy literacy learning that is more meaningful, contextual, and relevant to students' needs. The Independent Curriculum places numeracy mastery as one of the key competencies that teachers must have to support student learning outcomes. In response to this need, the Community Service Program (PKM) was designed with three main objectives, namely: (1) deepening teachers' understanding of the concept of numeracy literacy and its relevance in the Independent Curriculum; (2) developing teachers' skills in designing and implementing innovative numeracy literacy learning strategies; and (3) improving teachers' ability to utilize technology, such as learning applications and digital resources to support the learning process. Activities are carried out through training methods, intensive mentoring, and direct classroom practice involving 20 teachers of SDN Pondok Cabe Udik 01 as active participants. During the process, participants received conceptual materials, guidance on developing teaching materials, and supervision of their implementation in the field. The results of the activity showed significant improvements in understanding the concept of numeracy literacy, creativity in learning strategies, and skills in utilizing educational technology. In conclusion, this PKM program effectively improves teacher competency in numeracy literacy and has the potential to become a training model that can be replicated in various educational institutions..